A luta pela terra e a recriação dos espaços de vida de assentados na Campanha Gaúcha - Michele Lindner; Rosa Maria Vieira Medeiros (Confins)
The struggle for land and recreation life spaces amongst settlers in Campanha Gaúcha. The struggling for land in Brazil, organized by social movements, is already a historical issue and has been gaining more strength every day. The conquest of the land to a settler means build a “new territory”, an area of ownership, in other words the re-territorialization of this individual and his family. In this sense, this study aims to understand the adaptation of rural households after a migration, where the object of study settlements in Campanha Gaúcha in the state of Rio Grande do Sul, Brazil. Thus, the theoretical focus of the study focuses on topics relating to concepts of space, territory and and place, processes of desterritorialization and re-territorialization and social movements, and in the latter focus on a brief contextualization of the Movement of Landless Rural Workers – MLR (Movimento dos Trabalhadores Rurais Sem Terra – MST) in the state of Rio Grande do Sul. The information presented were obtained from data of – INCRA (National Institute of Colonization and Agrarian Reform) and in field researches that were done in settlements in the communities of São Gabriel, Santana do Livramento and Santa Margarida do Sul (agricultural places). The results obtained show how the territorial and social reorganization process was caused by the entry of settlements in traditional areas of large livestock rancher, and how it has modified the territory of Campanha Gaúcha by introducing new techniques and practices, through external factors. In addition, we try to demonstrate the differences between older and newer settlements. The consolidated infrastructure wanted by the settlers since the beginning until their production practices. However, it became clear that the importance of the conquest of “new land”, or “new territory”, as well as the importance of participation in a social movement lastedthis whole process of repossession which involves a strong adaptation of individuals to their new territory. This adaptation often requires rebuilding lives spaces, in other words, importing elements, customs and practices of an ancient territory and furthermore deployments of new practices and lessons learned throughout the process territorializing.